Spherical Crystallization: A Tool to Improve the Physicochemical Properties of APIs - Thenge, R. R; Chandak, M P; Adhao, V. S (Asian Journal of Pharmaceutical Research and Development, 2020)
A greater challenge in solid dosage formulation is the development of spherical agglomerates which increases the solubility and bioavailability of the drug. Spherical crystallization is “An agglomeration process that transforms crystals directly into compact spherical forms during the crystallization process.” Spherical crystallization is the novel agglomeration technique that can transform directly the fine crystals produced in the crystallization process into a spherical shape. Direct Compression of powders is simple and easy way of making tablets. In direct compression of Good Compressibility and flowability plays a major role. Spherical crystallization methods are very useful methods in which the drug crystals are modified using different solvents to directly compressible agglomerates. which cost effective and time saving. The different Techniques discussed are Crystallization method, Solvent crystallization method, Quasi- emulsion diffusion method, Ammonia Diffusion method, neutralization method, and solvent agglomeration technique. This article gives a detailed and comprehensive review about different techniques, its advantages, mechanism and application of Spherical agglomeration Technique along with its Evaluation and Characterization methods.